2014
DOI: 10.1183/09031936.00209313
|View full text |Cite
|
Sign up to set email alerts
|

Reliance on end-expiratory wedge pressure leads to misclassification of pulmonary hypertension

Abstract: Current guidelines recommend measurement of pulmonary artery wedge pressure (PAWP) at end-expiration. However, this recommendation is not universally followed and may not be physiologically appropriate. We investigated the performance of end-expiratory wedge pressure (eePAWP) in the evaluation of precapillary pulmonary hypertension patients. Three hundred and twenty-nine spontaneously breathing patients undergoing right heart catheterization were retrospectively classified as having precapillary, postcapillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 48 publications
1
48
0
2
Order By: Relevance
“…Overall, 29% of patients with a pre-capillary phenotype would have been misclassified as having post-capillary PH, based on measurement of end-expiratory PAWP ( fig. 4) [30]. However, the end-expiratory method is supported by an earlier study, which showed that use of digitised PAWP (measured by the automated computer) instead of end-expiratory PAWP resulted in the misdiagnosis of nearly 30% of PH group 2 patients as having PAH [31].…”
Section: Pitfalls In Pawp Measurementmentioning
confidence: 77%
See 2 more Smart Citations
“…Overall, 29% of patients with a pre-capillary phenotype would have been misclassified as having post-capillary PH, based on measurement of end-expiratory PAWP ( fig. 4) [30]. However, the end-expiratory method is supported by an earlier study, which showed that use of digitised PAWP (measured by the automated computer) instead of end-expiratory PAWP resulted in the misdiagnosis of nearly 30% of PH group 2 patients as having PAH [31].…”
Section: Pitfalls In Pawp Measurementmentioning
confidence: 77%
“…The use of end-expiratory PAWP, while recommended by the ESC/ERS guidelines, remains a subject of debate [30,31]. In a recent retrospective analysis of 329 spontaneously breathing patients who underwent RHC, tracings were evaluated to compare end-expiratory PAWP readings with those obtained when PAWP was averaged throughout the respiratory cycle [30].…”
Section: Pitfalls In Pawp Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Wydaje się, że końcowowydechowe pomiary PAWP są lepsze do różnicowania między PAH i HFPEF, zaś wartości średnie są bardziej dokładne w grupie chorych z przewlekłą obturacyjną chorobą płuc (COPD, chronic obstructive pulmonary disease), u których wahania oddechowe są zwykle większe. W praktyce klinicznej błędnych klasyfikacji PH-LHD jako PAH i niewłaściwego leczenia tych pacjentów lekami celowanymi dla PAH jest istotnie więcej niż na odwrót [23,24].…”
Section: Rozpoznanie Ph -Metody Nieinwazyjne I Inwazyjne Oraz Ich Ogrunclassified
“…75 It has been suggested that using digitalized mean PAWP instead of end-expiratory PAWP may underestimate true LA pressure; 76 however, others have reached the opposite conclusion. 77 If in doubt, wedge position may be confirmed by blood oxygen saturation equal to systemic saturations, taken from catheter tip with the balloon inflated. 78 It should be recognized that PAWP may overestimate LA pressure, 79 and one must be cautious in interpreting raised PAWP in the setting of a normal-sized LA.…”
Section: Rhcmentioning
confidence: 99%